Systematic mapping of the literature on hackathons - Costa, Giannina; García-Holgado, Alicia; Alvarez, Pamela (Frontiers in Education, 2026)
IntroductionHackathons have evolved from programming events to multidisciplinary pedagogical tools in educational settings, demanding structured methodological frameworks to maximize their educational impact. However, there is limited systematization regarding the methodological approaches implemented in student contexts.MethodsThis study conducted a systematic mapping of the literature to identify and categorize methodological frameworks used in student hackathons, analyzing their organizational structures, evaluation metrics, and reported outcomes. The review followed PRISMA guidelines and consulted three databases (Scopus, Web of Science, IEEE Xplore) for the period 2014–2024. Specific inclusion criteria for student hackathons were applied, resulting in 37 primary studies that met the established quality threshold (score ≥ 5/8).ResultsFive main categories of hackathons were identified: educational/curricular (48.6%), thematic/specialized (32.4%), civic/social (13.5%), and academic research (5.4%). The most frequent methodological frameworks were Design Thinking, agile methodologies, and Challenge-Based Learning. Predominant evaluation metrics included socio-educational impact, number of participants, participant satisfaction, lessons learned, and skills development. Outcomes were classified as tangible (mainly prototypes, projects, MVPs, and products) and intangible (soft skills development, business ideas, and entrepreneurial skills).Discussion and conclusionsStudent hackathons exhibit methodological diversity, with no consensus on standardized frameworks. Hybrid methodological approaches appear more effective in achieving educational objectives. Further research is needed to address project sustainability and long-term impact evaluation.